Factors Leading to the Decline and Slow Progress of Learners' Standards in English as a Foreign Language in Tabuk University: A Case Study -The University College of Umluj – Male Section (المجلة الدولية للبحوث العلمية, 2025)
The decline and slow progress of the learners' standard who major in English language in the university college of Umluj Male Section necessitate carrying out this study. Based on this view, first, the impacts of the environment where learning takes place. Second, the teaching-learning techniques adopted by the teachers and students respectively. Third, the personal traits of the learners. These above-mentioned factors are the focal point of this research paper. The tools used to collect data were questionnaires. Specific questionnaires were designed for the lecturers and other ones were designed for the students. The population of the study involved 10 teachers and 70 students selected randomly. The findings of the study revealed the fact that the factors investigated have paramount impacts on the students' performance and language proficiency as well as the teachers' performance. As a result, the findings are essential for those who engage in decision-making in the college and similar groups. The Ministry of Education, private institutions as well as individuals whose concerns include teaching or learning English as a foreign language could find the findings useful, significant and feasible. Furthermore, the findings could be of great benefits to the researchers whose fields of enquiry require some information about the effects of those investigated factors.